EVALUASI PELAYANAN INFORMASI OBAT PASIEN RAWAT JALAN DI PUSKESMAS KARTASURA KABUPATEN SUKOHARJO JAWA TENGAH - Riska Chandra Pradana (Jurnal Penelitian Farmasi & Herbal, 2023)
Pharmaceutical services at the public health center play an important role in the implementation of efforts to improve public health, one of which is the provision of drug information services to support drug use with the aim of successful treatment. The objective of this study was to assess outpatient drug information services at the Kartasura Health Center. This type of research is a descriptive observational research that is quantitative in nature using a questionnaire sheet of 96 respondents. Kartasura Public Health Center related to the provision of drug information to outpatients has been carried out, but there is still drug information that has not been conveyed by pharmacists or 0% is not conveyed, namely stability and contraindications. The drug information points that were transmitted to the specific drug are the drug name at 100%, the dosage form at 100%, the drug dose at 100%, the method of use at 98.96%, and the indications at 97.92%. The drug information points that were submitted, but only for some drugs, were storage rules at 86%, side effects at 57%, and interactions at 19%.